A Single-institution Study on Predictors of Short-term Progression from Mild Cognitive Impairment in Parkinson’s Disease to Parkinson’s Disease with Dementia - Tajiri, Yuki (Yonago Acta Med, 2020)
BACKGROUND: Patients with non-demented Parkinson’s disease (PD) sometime have mild cognitive impairment (MCI), and mild cognitive impairment in Parkinson’s disease (PD-MCI) may convert to Parkinson’s disease with dementia (PDD) within several years. Cognitive impairment also occurs in the early stages of the disease, gradually progressing to lower quality of life and instrumental activities of daily living. It is important to elucidate the predictors of progression from PD-MCI to PDD via longitudinal studies. METHODS: This was a single center, case-control study. We analysed data from 49 patients with PD-MCI diagnosed as level I using the Movement Disorder Society PD-MCI criteria at baseline who had completed 1.5 years of follow-up. We defined patients who progressed to PDD as patients with progressive PD-MCI and patients who did not progress to PDD as patients with non-progressive PD-MCI. Depression, apathy, sleep disorders, constipation, light-headedness, hallucinations, impulse control disorders (ICDs) and impulsive–compulsive behaviors (ICBs) at baseline were statistically analysed as predictors of progression. RESULTS: Of the 49 PD-MCI patients, 33 did not convert to PDD (non-progressive PD-MCI), and 16 converted to PDD (progressive PD-MCI). The Mini-Mental State Examination (MMSE) score, light-headedness and ICDs were elucidated as predictors of progressive PD-MCI via a multivariate logistic regression model. The adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for each item were MMSE score, OR 0.324, 95% CI 0.119–0.882, P = 0.027; light-headedness, OR 27.665, 95% CI 2.263–338.185, P= 0.009; and ICDs, OR 53.451, 95% CI 2.298–291.085, P = 0.010. CONCLUSION: Cognitive function, ICDs and light-headedness may be risk factors for the development of PDD in PD-MCI patients.